Umbilical Cord Care in the Newborn Infant. - Al-Nouri, Luay A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The umbilicus, before and shortly after sloughing of the cord, can be a source of infection or toxicity. The infection can be severe, such as septicaemia or tetanus neonatorum. Method: Mothers of 200 neonates seen at the Children Welfare Hospital, outpatient department, Baghdad, and at Al-Takia health centre, Baquba, were interviewed about the separation of the umbilical stump and the care of the umbilicus after delivery at home or hospital, in the period, January to July 2003, excluding March and April, the time of active military invasion of the country. Results: For occlusion of the cord a plastic clamp was used in all hospital deliveries, and 80% of home deliveries. A cotton thread or a surgical silk were used for the others. The stump separation was as early as the second day after birth or as late as the 25th .day, but it was most commonly on the seventh day after birth. (Mean 9.5 +/- SD 10.5) A variety of substances were applied to the umbilicus, included azarcon, alcohol, kohl, and charcoal. Almost forty per cent of the mothers did not receive any tetanus toxoid. Conclusion: Mothers may be assured that occasionally a normal stump separation may be as late as 25th day after birth. Many of the present practices at home in the care of the umbilicus may form a real risk of infection and toxicity.